The great railroad race the diary of Libby West - Gregory, Kristiana (New York Scholastic Inc., 1999)
As the daughter of a newspaper reporter, fourteen-year-old Libby keeps a diary account of the exciting events surrounding her during the building of the railroad in the West in 1868.
Keywords: Frontier and pioneer life -- West (U.S.) -- Fiction; Diaries -- Fiction; West (U.S.) -- Fiction